Effect of Alkaline and Hot Water Treatments on the Structure and Morphology of Piassava Fibers - Santos,Eduardo Braga Costa (2018)
The effect of alcaline and hot water surface treatments of piassava Attalea funifera fibers was investigated. The efficiency of each treatment was evaluated by Fourier transform infrared spectroscopy, X-ray diffractometry, optical microscopy, scanning electron microscopy and atomic force microscopy. The alkaline treatments were effective in removing the superficial lignin layer from the fiber, while the hot water treatment was not. Treatment with hot water and NaOH caused fiber defibrillation. NaOH was most effective in promoting both, a decrease in fiber diameter and an increase in fiber surface area. Treatment with Ca(OH)2 led to the formation of a CaCO3 layer deposited on the fiber, preventing defibrillation. The crystalline structure of the fiber was not altered by any of the treatments, maintaining type I cellulose.